Multi-Criteria Decision Model based on AHP and Linguistic Information - Karanik, Marcelo J. (2014)
Multi-Criteria Decision Analysis (MCDA) is a usual activity among organisations and decisions related to people’s activities. Due to the complexity of considering multiple criteria, to select an alternative is a non-trivial task. From operative levels to managerial ones, MCDA is implemented by using several (formal and informal) techniques. Two useful techniques that help to make a decision are the Analytic Hierarchy Process (AHP) and MCDA models based on Linguistic Information (LI). This work describes a MCDA framework that combines the mentioned techniques in order to provide more confidence in the decision making process. To test the proposed model, framework was used to select the adequate network configuration to improve quality of service (QoS). Finally, the framework’s outputs were compared to real experts’ opinions obtaining satisfactory results. Keywords: IPv6 deployment, IPv6 transition solutions, performance analysis, DNS64, TOTD, security, cache poisoning attack, random permutation.